Understanding Diaspora Pasifika (Sāmoan and Tongan) Intergenerational Sense-Making and Meaning-Making through Imageries - Faleolo, Ruth (Lute); Faleolo, Sh’Kinah Tuia‘ana Nauna; Faleolo, Lydiah Malia-Lose (Art/Research International)

(untitled) (University of Alberta, 2024)
This article presents imagery representative of Pasifika (Sāmoan and Tongan) diaspora (nofo ‘i fafo o Sāmoa/ tu‘a Tonga) intergenerational sense-making and meaning-making. The main author, Ruth (Lute) Faleolo, presents a selection of eleven photographs shared with her by Pasifika knowledge holders across Aotearoa (New Zealand), Australia, and the United States, alongside six personally photographed people/events in Aotearoa. Collectively, these images show important Pasifika meaning-making and sense-making processes that are occurring intergenerationally in tu‘a Tonga/ nofo ‘i fafo o Sāmoa. These selected images were collected as part of an ongoing larger study of Pasifika migration and mobilities (2013-2023). The second author, Sh’Kinah Tuia‘ana Nauna Faleolo, presents pieces from her art collection (2015): Two Woven Identities and discusses her meaning-making and Indigeneity enfolding these pieces while growing up in Aotearoa. The third author, Lydiah Malia-Lose Faleolo, presents her Identity artwork (2019) and Duality design pieces (2023) that demonstrate her current and continued Indigeneity as a Sāmoan Tongan woman, living and studying in Australia. The fourth author, Nehemiah Thomas Faleolo’s artistic expressions captured in his annotated sketches and sculpture work were selected from a collection he had created in Australia. Nehemiah’s respected artwork and meaning-making, carefully documented by him in 2020 was (posthumously) selected by Faleolo family members, from his private exhibition and collection (Brisbane). Scanned documents and photographs stored on his mobile device have been contributed to this article on his behalf, with permission.For many Pasifika living in Aotearoa, Australia and the United States, the processes of intergenerational sense-making and meaning-making occur in the diaspora contexts of faith, family, community, and education. The imageries presented by Ruth (Lute) Faleolo follow these thematic contexts, with short analyses about the intergenerational sense-making and meaning-making observed per photo. The purpose of her contribution to the discussion is to promote imageries as a way of conveying Pasifika understandings and knowledge. Sh’Kinah Tuia‘ana Nauna Faleolo, Lydiah Malia-Lose and Nehemiah Thomas Faleolo’s contributions present personal accounts of intergenerational sense-making and meaning-making as experienced through their artistic expressions, within nofo ‘i fafo o Sāmoa/ tu‘a Tonga contexts of Aotearoa and Australia.